The Zen Experience - Hoover, Thomas, 1941- (Salt Lake City, UT : Project Gutenberg, 2010)
"The Zen Experience" by Thomas Hoover is a historical account written in the late 20th century. The text explores the evolution of Zen Buddhism, tracing its origins from Indian Buddhism and Chinese Taoism through several key figures such as Bodhidharma and Hui-neng, culminating in its development and impact in Japan. Hoover aims to illuminate Zen as a practical philosophy shaped by the experiences of its masters rather than dwelled upon through theoretical teachings. At the start of the work, Hoover introduces the foundational concepts of Zen, emphasizing its reliance on personal experience over mere intellectual abstraction. The opening portion delves into the historical roots of Zen, highlighting the influence of noted figures like Lao Tzu and the Buddha, while setting the stage for the arrival of Bodhidharma in China$1 (Bdeemed the First Patriarch of Zen. Through anecdotes and principles, the text suggests a dichotomy between rational and intuitive thought, presenting Zen not only as a philosophy but as a means of experiencing a deeper existence beyond conventional perception. (This is an automatically generated summary.)s
Release date is 2010-11-14
Produced by Al Haines
Keywords: Zen Buddhism -- History; Zen priests -- Biography